New genetic findings in schizophrenia: is there still room for the dopamine hypothesis of schizophrenia? - Nieratschker, Vanessa; Nöthen, Markus M.; Rietschel, Marcella (Frontiers in Behavioral Neuroscience, 2010)
Schizophrenia is a highly heritable disorder, but the identification of specific genes has proven to be a difficult endeavour. Genes involved in the dopaminergic system are considered to be major candidates since the “dopamine hypothesis” of impairment in dopaminergic neurotransmission is one of the most widely accepted hypotheses of the aetiology of schizophrenia. The overall findings from candidate studies do provide some support for the “dopamine hypothesis”. However, results from the first systematic genome-wide association (GWA) studies have implicated variants within ZNF804A, NRGN, TCF4, and variants in the MHC region on chromosome 6p22.1. Although these genes may not immediately impact on dopaminergic neurotransmission, it remains possible that downstream impairments in dopaminergic function are caused. Furthermore, only a very small fraction of all truly associated genetic variants have been detected and many more associated variants will be identified in the future by GWA studies and alternative approaches. The results of these studies may allow a more comprehensive re-evaluation of the dopamine hypothesis.